Effectiveness of the IDEAL Problem Solving Model Based onOpen-Ended Questions onthe Creative Thinking Skills of Grade VII Students - Karmila Dewi Santika; Suciati Suciati; Bayu Antrakusuma (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
AbstractThe ability to think creatively plays important role in students’self development in the 21st century. This study aims to determine the effectiveness of the IDEAL Problem Solving learning model based on open-ended questions on students' creative thinking abilities. This study is a quantitative quasi-experimental study with a Pretest-Posttest Control Group Design. The subjects of this research were class VII students of SMP Negeri 3 Kartasura which consisted of 64 students. Clusters random sampling was used as the sampling method. Data collection was carried out using test techniques in the form of pretest and posttest as well as non-test techniques in the form of observation and documentation. Analysis of the research data was carried out by normality test, homogeneity test, independent sample t-test and n-Gain test with the help of SPSS 23. The hypothesis test with the independent sample t-test showed the number 0.000, which means H0 was rejected and H1 was accepted, meaning that the IDEAL Problem Solving learning model is effective increasing student’s creative thinking. Skills. The n-gain test in the experimental class was 0,56 (effective enough), while in the control class the n-gain percentage was 0,08 (ineffective) where the experimental class used the IDEAL Problem Solving model so that it can be concluded that the IDEAL Problem Solving Model quite effective in improving the creative thinking skills of class VII students at SMP Negeri 3 Kartasura in the subject matter of Science Objects and Its Observations.Keywords: Learning Model, IDEAL Problem Solving, Creative ThinkingKemampuan berpikir kreatif berperan penting dalam pengembangan diri siswa pada abaf 21. Tujuan penelitian ini adalah untuk mengetahui keefektifan model pembelajaran IDEAL Problem Solving berbasis soal open-ended terhadap kemampuan berpikir kreatif siswa. Penelitian ini merupakan penelitian kuantitatif kuasi eksperimen dengan rancangan pretest-posttest control group design. Subyek penelitian ini adalah siswa kelas VII SMP Negeri 3 Kartasura yang teridiri dari 64 siswa. Pengambilan sampel dilakukan menggunakan cluster random sampling. Pengumpulan data dilakukan dengan menggunakan teknik tes berupa pre-test dan post-test dan teknik non-test berupa observasi dan dokumentasi. Analisis data penelitian dilakukan dengan uji normalitas, uji homogentitas, uji independent sample t-test dan uji n-Gain dengan bantuan SPSS 23. Uji hipotesis dengan independent sample t-test sebesar 0,000 yang berarti H0 ditolak dan H1 diterima, artinya model pembelajaran IDEAL Problem Solving efektif dalam meningkatkan kemampuan berpikir kreatif siswa. Uji n-gain kelas eksperimen sebesar 0,56 (cukup efektif), sedangkan kelas kontrol persentase n-gain sebesar 0,08 (tidak efektif) dimana kelas eksperimen menggunakan model IDEAL Problem Solving sehingga memberikan keismpulan bahwa Model IDEAL Problem Solving cukup efektif dalam meningkatkan kemampuan berpikir kreatif siswa kelas VII di SMP Negeri 3 Kartasura pada materi Objek IPA dan Pengamatannya.